2008
DOI: 10.1007/s10549-008-0164-5
|View full text |Cite
|
Sign up to set email alerts
|

Survivin plays as a resistant factor against tamoxifen-induced apoptosis in human breast cancer cells

Abstract: Tamoxifen has been the mainstay of endocrine therapy for estrogen receptor-positive breast cancer. However, approximately 40% of breast cancer patients do not respond to tamoxifen treatment. Further, most tumors eventually acquire tamoxifen resistance. Therefore, it is necessary to develop effective modalities to enhance the efficacy of tamoxifen in breast cancer treatment. In this study, we investigated the mechanism by which breast cancer cells develop resistance against tamoxifen from the viewpoint of tamox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…Earlier studies have shown that TAM may also act on the mitochondria to induce apoptosis [12,21]. Recent studies have used a low concentration of TAM (5 mmol/l) in combination with another drug (lovastatin) in MCF-7 [22,23]. Hoechst staining on A375 cells treated with TAM at both its effective concentration (10 mmol/l) and half-effective concentration (5 mmol/l) resulted in a very small increase in apoptosis compared with control (Fig.…”
Section: Synergistic Effect Of Tamoxifen and Pst In Inducing Apoptosimentioning
confidence: 99%
“…Earlier studies have shown that TAM may also act on the mitochondria to induce apoptosis [12,21]. Recent studies have used a low concentration of TAM (5 mmol/l) in combination with another drug (lovastatin) in MCF-7 [22,23]. Hoechst staining on A375 cells treated with TAM at both its effective concentration (10 mmol/l) and half-effective concentration (5 mmol/l) resulted in a very small increase in apoptosis compared with control (Fig.…”
Section: Synergistic Effect Of Tamoxifen and Pst In Inducing Apoptosimentioning
confidence: 99%
“…Overexpression of inhibitor of apoptosis proteins (IAPs) has been shown as a hallmark of many types of cancer, including breast cancer . IAPs, particularly Survivin and XIAP, are frequently associated to a poor prognosis (Span et al, 2004;Hinnis et al, 2007;Jaffer et al, 2007;Zhang et al, 2011) and drug resistance in neoplastic mammary cells (Moriai et al, 2009;Dean et al, 2009;Flygare et al, 2012;Wang et al, 2010;Zhu et al, 2010). Thus, they have been extensively studied as potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has indicated that survivin expression plays an essential role in drug resistance and that genetic or pharmacological modulation of survivin expression affects drug effectiveness in apoptosis induction (Li and Ling 2006;Moriai et al 2008). In endothelial cells (ECs), VEGF can up-regulate survivin expression through the PI3 K/Akt signaling pathway to escape from apoptosis (O'Connor et al 2000), which can be suppressed by survivin targeting treatment (Mesri et al 2001).…”
Section: Introductionmentioning
confidence: 99%